Prescription History Before Opioid Overdose Death: PDMP Data and Responsible Prescribing. Issue 4 (July 2021) - Shreffler, Jacob; Shaw, Isaac; Berrones, Adam; Huecker, Martin
Abstract : Introduction: As the opioid epidemic continues, state legislatures and clinicians increasingly utilize Prescription Drug Monitoring Programs (PDMPs). These programs record dates prescribed and filled for all controlled substances, attempting to identify high-risk prescribing. The aims of this study were to (i) examine data from individuals who died of accidental opioid overdose and (ii) compare differences between those with prescriptions documented in Kentucky's PDMP with individuals without recorded prescriptions. Methods: This was a retrospective, observational cohort study conducted in Jefferson County, Kentucky. We reviewed records for all opioid overdose death subjects from 2017 and 2018, cross-referencing with prescriptions in Kentucky's PDMP (Kentucky All Schedule Prescription Electronic Reporting System [KASPER]) back to 2014. We performed χ 2 analyses for categorical variable comparisons and a separate univariate analysis for age. Results: Of the 575 individuals who died of accidental opioid overdose in Jefferson County during the study period, 379 (65.9%) had prescriptions documented in KASPER. Individuals had a high prevalence of fentanyl on postmortem toxicology. Only one individual had postmortem toxicology positive for buprenorphine, a medication for opioid use disorder (MOUD). Several subjects experienced what we termed see-saw MOUD prescribing (prescriptions alternating between MOUD and other controlled substances including full agonists), and multiple prescriptions were apparently written and/or filled for deceased subjects. Conclusions: Review of PDMP data in deceased patients can prevent unnecessary opioid prescribing and optimize clinical practice. Buprenorphine may have a protective effect in opioid dependence, but access must be consistent. Providers should be aware of see-saw MOUD prescribing and understand the effects on patient care. In response to the prescriptions filled for deceased individuals, legislators could enact a policy such as Void All Prescriptions or VAP alerts to cancel all prescriptions for individuals who have died, reducing drug diversion. It is vital that providers routinely use PDMP data along with counseling and other treatment strategies to optimize patient care.